PERAN EDUKATIF CORPORATE SOCIAL RESPONSIBILITY (CSR) DALAM PEMBERDAYAAN USAHA MIKRO DAN KECIL MENUJU KEBERLANJUTAN (SUSTAINABLE) STUDI KASUS PADA PT POS INDONESIA - Fatimah Syawalia Noptiani; Elly Malihah; Mirna Nur Alia Abdullah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the educational role of Corporate Social Responsibility (CSR) implemented by PT Pos Indonesia in empowering Micro and Small Enterprises (MSEs). The research is motivated by the gap between the conceptual framework of CSR as a sustainable capacity-building instrument and its practical implementation in the field. The objective of this study is to analyze how CSR functions as an educational process in empowering MSEs toward sustainability. This study employs a qualitative approach with a case study design, involving five informants consisting of three MSE partners and two CSR managers. Data were collected through in-depth interviews, observations, and literature studies, supported by bibliometric analysis to map research trends related to CSR and empowerment. The findings reveal that CSR has provided educational support through training and business facilitation; however, its implementation remains limited, as the training is not continuous and not fully aligned with the specific needs of MSEs. In addition, the lack of sustained mentoring results in a fragmented learning process, leading MSEs to rely more on individual experience rather than structured program support. From a theoretical perspective, the CSR program is still positioned at the enabling stage rather than fully achieving empowering, as it has not yet developed into an integrated and sustainable learning system. Therefore, the study highlights the importance of strengthening continuous training and mentoring to enhance the effectiveness of CSR as an educational instrument in empowering MSEs.